Peningkatan Kemampuan Mitigasi Bencana Erupsi Merapi bagi Siswa Tunanetra Studi Kasus di SLB Negeri 1 Sleman - Imanuel Adi Papa Yohanes, Kristi Dese; Zulfa, Alfiatus; Kahfi, Ashabul; Benardi, Andi Irwan (Edu Geography, 2019)
Sleman Special School 1 is a special school for disabled students in the Special Province of Yogyakarta. Geographically, the school is within a 12-15 kilometer radius from the top of Mount Merapi. The lack of learning media related to disaster mitigation makes blind students not yet have an understanding and preparedness in facing disaster risk. The method used in this community research is the PALS (Participatory Action and Learning System) which places blind class students and teachers as the subject and object directly in the process of awareness, capacity building, mentoring to institutionalization. On of the, The results of this study the creation of disaster mitigation learning media in the form of a Volcano Blind Map model and increased space reading ability, mitigation, and preparedness for blind students in facing disaster risks of Merapi eruption.